Screening and loan origination time: Lending standards, loan defaults and bank failures - Mikel Bedayo; Gabriel Jiménez; José Luis Peydró; Raquel Vegas (ZBW - Leibniz Information Centre for Economics, 2023)
We show that loan origination time is crucial for bank lending standards over the credit cycle, as well as for ex-post loan-level defaults and bank-level failures. We use the credit register in Spain for the business loans over the 2002-15 period focusing on the time of a loan application and its granting. First, when VIX is low (proxying for good times) banks shorten the time to originate a loan, particularly to less-capitalized (riskier) firms. Results suggest that bank moral hazard incentives are a key mechanism. Shorter loan origination time to ex-ante riskier firms in good times is especially stronger for: (i) banks with less capital (proxying for moral hazard problems between bank owners and taxpayers/debtholders); (ii) non-listed banks (proxying for moral hazard problems between bank management and shareholders); (iii) loans to firms in geographical areas which do not form the bank's main market and experience a real estate bubble (proxying for moral hazard problems between local loan officers and the bank headquarter), mainly if those areas have more bank competition; or, relatedly, stronger effects on loans granted to firms operating in industries which the bank is not most specialized at (proxying for moral hazard problems between different parts within the bank). Second, shorter loan origination time is associated with higher ex-post defaults at the loan-level, and aggregated at the bank-level, with higher likelihood of bank failure or other strong bank distress events, overall consistent with lower screening (time).
Keywords: G01; G21; G28; E44; E51; 330; loan origination time; credit standards; credit cycle; defaults; banks; screening; moral hazard